2020
DOI: 10.21203/rs.3.rs-35019/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of COVID-19 in high burden countries for HIV/TB: A systematic review of evidence

Abstract: Background: The triple burden of COVID-19, tuberculosis and human immunodeficiency virus is one of the major global health challenges of the 21st century. In high burden HIV/TB countries, the spread of COVID-19 among people living with HIV is a well-founded concern. A thorough understanding of HIV/TB and COVID-19 pandemics is important as the three diseases interact. This may clarify HIV/TB/COVID-19 as a newly related field. However, several gaps remain in the knowledge of the burden of COVID-19 on patients wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 50 publications
1
26
0
2
Order By: Relevance
“…Establishing this baseline before the indirect effects of the COVID-19 pandemic have been fully realised is also crucial, because these effects might bear on the recalibration of future targets. 4,5 Measurable targets relating to incidence and deaths have been proposed to assess progress in HIV, but they have not been synthesised to provide a comprehensive assessment of HIV burden. The original 90-90-90 targets were proposed in 2014, 6 and set out that by 2020, 90% of people living with HIV will know their HIV status, 90% of those who are aware of their HIV-positive status will have initiated antiretroviral therapy (ART), and 90% of those on treatment will be virally suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing this baseline before the indirect effects of the COVID-19 pandemic have been fully realised is also crucial, because these effects might bear on the recalibration of future targets. 4,5 Measurable targets relating to incidence and deaths have been proposed to assess progress in HIV, but they have not been synthesised to provide a comprehensive assessment of HIV burden. The original 90-90-90 targets were proposed in 2014, 6 and set out that by 2020, 90% of people living with HIV will know their HIV status, 90% of those who are aware of their HIV-positive status will have initiated antiretroviral therapy (ART), and 90% of those on treatment will be virally suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…33,36,37 According to a recent meta-analysis, the presence of underlying TB infection was identified as a risk factor for COVID-19 infection, increasing its severity and mortality rates, and decreasing disease recovery. 38 In contrast, another meta-analysis showed that patients with present TB were not more vulnerable to get infected with COVID-19 or to higher mortality rates; however, the same study acknowledged that there was a 2.1-fold increase in the risk of developing severe forms of COVID-19 disease, with no statistical significance. 39 It should be mentioned that the latter study included a small number of TB patients with COVID-19 co-infection and the risk of bias was not assessed in a rigorous way.…”
Section: Impact Of Covid-19 On Tb Patientsmentioning
confidence: 96%
“…As of now, there have not been any official diagnostic recommendations for identifying TB in patients infected with COVID-19. However, a meta-analysis study recommended dual testing with COVID-19 real-time RT-PCR and Xpert MTB/RIF assay 84 . We would recommend testing patients synergistically for Latent TB infection and COVID-19 in endemic regions.…”
Section: Implications and Recommendationsmentioning
confidence: 99%